2019
DOI: 10.1002/mgg3.754
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the relation between IL2RA/IL2RB and rheumatoid arthritis risk

Abstract: Background The biological mechanisms driving disease chronicity in rheumatoid arthritis (RA) are largely unidentified. Therefore, we aimed to determine genetic risk factors for RA. Methods In this case–control study, which includes samples from 499 patients and 507 healthy controls, six single‐nucleotide polymorphisms (SNPs) in interleukin‐2 receptor subunit alpha ( IL2RA ) and IL2RB were selected. Genotyping was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
(25 reference statements)
0
5
1
Order By: Relevance
“…For instance, the absolute risk of RA at 65 years was found to be between 30.6% (95% CI = 18.5%–42.6%) and 53.8% (95% CI = 42.8%–64.9%) within the top 5% of the PRS distribution. Our PRS showed a higher estimate (OR = 1.55; 95% CI = 1.27–1.90) among high PRS individuals than the association of rare variants in IL2RA and IL2RB with RA risk reported in previous studies 26,27 …”
Section: Discussioncontrasting
confidence: 49%
“…For instance, the absolute risk of RA at 65 years was found to be between 30.6% (95% CI = 18.5%–42.6%) and 53.8% (95% CI = 42.8%–64.9%) within the top 5% of the PRS distribution. Our PRS showed a higher estimate (OR = 1.55; 95% CI = 1.27–1.90) among high PRS individuals than the association of rare variants in IL2RA and IL2RB with RA risk reported in previous studies 26,27 …”
Section: Discussioncontrasting
confidence: 49%
“…In the Chinese Han population, Yang Y et al. found an association between IL2RA and a decreased risk of RA ( 51 ). Furthermore, IL2RA has been identified as a susceptibility gene for autoimmune thyroid disease ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that in patients with AS, CX3CR1 + monocytes have a specific proinflammatory transcriptome and actively participate in the activation and expansion of ILC3s, thus promoting the persistent proinflammatory status of AS [ 26 ]. The IL2RB gene is a cytokine signalling-related gene [ 27 ] that encodes the receptor of interleukin 2 (IL-2) and is associated with autoimmune and inflammatory diseases [ 28 ]. A study found that an IL2RB polymorphism (rs2281089) significantly reduced the risk of RA [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IL2RB gene is a cytokine signalling-related gene [ 27 ] that encodes the receptor of interleukin 2 (IL-2) and is associated with autoimmune and inflammatory diseases [ 28 ]. A study found that an IL2RB polymorphism (rs2281089) significantly reduced the risk of RA [ 28 ]. A 10-year follow-up study of AS patients found that 14 single-nucleotide polymorphisms (SNPs) in 10 different genes distributed in AS patients were significantly associated with peripheral arthritis (PA) and that IL2RB was one of the 10 genes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%